2014
DOI: 10.1111/jan.12471
|View full text |Cite
|
Sign up to set email alerts
|

Community reintegration of stroke survivors: the effect of a community navigation intervention

Abstract: Results will describe experiences and outcomes of a community navigation intervention. Engagement of multiple stakeholders has the potential to develop a shared understanding of community reintegration and generate evidence informed recommendations for service enhancement at critical points in stroke recovery to support survivor and community well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…However, the efficacy and theoretical underpinnings of these interventions to support multiple behavioral changes are unclear. The results of a mixed methods study of a tailored self-management program showed promise in promoting patient activation, exercise, and healthy eating (Montgomery et al, 2015). Future studies should incorporate objective and self-report measures of healthy behaviors to determine whether self-management interventions can promote multiple health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy and theoretical underpinnings of these interventions to support multiple behavioral changes are unclear. The results of a mixed methods study of a tailored self-management program showed promise in promoting patient activation, exercise, and healthy eating (Montgomery et al, 2015). Future studies should incorporate objective and self-report measures of healthy behaviors to determine whether self-management interventions can promote multiple health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The terms "reintegration," "cancer," and "definition" were also investigated using Google's search engine to supply dictionary definitions, encyclopedia compendiums, and current uses of the term. International sources identified within the databases included supporting literature from the Government of Canada (Griffiths, Dandurand, & Murdoch, 2007), United Nations Office on Drugs and Crime (2006), the International Organization for Migration (2017) and published research articles conducted in other countries such as Canada (Kelly et al, 2016;Montgomery et al, 2015;Wood-Dauphinee & Williams, 1987) and the United Kingdom (Eshareturi, Serrant-Green, Bayliss-Pratt, & Galbraith, 2014;Pini, Gardner, & Hugh-Jones, 2013). Basic database searches using the term "reintegration" initially yielded the following results: CINAHL 2,770 results, PubMed 3,124 results, PsycINFO 21,440 results, JSTOR 886 results, and Google Scholar 298,000 results.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The nursing discipline has predominantly used reintegration in studies for military personnel (Doherty & Scannell-Desch, 2015), stroke survivors (Montgomery et al, 2015), ex-prisoners (Eshareturi et al, 2014;Marlow & Chesla, 2010), mental health conditions (Gibson, 1999), and pediatric cancer survivor populations (Labay et al, 2004;Libman, Sherrod, & Weyant 2017;Pini et al, 2013). In the context of cancer survivorship, literature focuses on adult survivors' return to work (Clark & Landis, 1989), and pediatric survivors' return to school (Labay et al, 2004;Libman et al, 2017;Pini et al, 2013).…”
Section: Nursing and Reintegrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficacy and theoretical underpinnings of these interventions to support multiple behavioral changes are unclear. The results of a recent mixed methods study of a tailored self-management program showed promise in promoting patient activation, exercise, and healthy eating (Montgomery et al 2015). Future studies should PeerJ reviewing PDF | (2016:12:15018:1:1:ACCEPTED 17 Mar 2017)…”
Section: Addressing Purpose 3: Developing Multiple Behavior Change Inmentioning
confidence: 99%